Nao control on multi-annual periodicities in water resources and their utility for managing water resource extremes. - Rust, William (Cranfield University, 2021)
Water scarcity and the hazard of drought impacts millions of people worldwide, highlighting the need for robust water resource management. Forecasting of water resources (i.e., groundwater and streamflow) aids in the planning and preparedness for water resource extremes which, in turn, can help mitigate their societal and economic impacts. With the effects of climate change expected to exacerbate certain water resource extremes, there is increased pressure to develop improved ways to estimate future water resource behaviour. Hydrometeorological conditions in Europe are modulated by the North Atlantic Oscillation with important multiannual periodicities. Existing studies have shown that the NAO can drive multiannual periodicity behaviour in water resources and influence the timing of water resource extremes such as drought. As such, it has been discussed in hydroclimate literature that these multiannual relationships may have some utility in water resource forecasting applications. However, a systematic assessment of the relationship between the NAO and wide-scale water resources, at multiannual periodicities, has yet to be undertaken for large water resource datasets. Therefore, there is limited information to develop significant relationships between catchment properties and water resource response to multiannual NAO periodicity (e.g., magnitude, or lags), which may be of value in forecasting applications. The aim of this PhD thesis is to assess the feasibility of a relationship between the NAO and water resource variables, at multiannual periodicities, for indicating water resource behaviour (including extremes), at seasonal to multiannual timescales. This has been achieved using large hydrological datasets in the UK and the wavelet transform to characterise periodicities in these records and the NAOI. This research demonstrates that a significant and wide-spread ~7-year periodicity is exhibited by most UK water resources and has a significant relationship with the NAOI. Research presented here show that the degree of influence of this ~7-year periodicity is considerable, affecting groundwater median regional groundwater level anomalies by up to 0.71sd, and median regional streamflow anomalies by up to 0.55sd. These anomalies are also comparable to the projected effects of climate change on UK water resources. Findings demonstrate that there are notable non-stationarities of this multiannual NAO periodicity and its relation to UK water resource variables, with the ~7-year periodicity detected in water resources only being dominant since the 1970s. This has important implications for the applicability of existing water resource forecasting systems that have utilized data from this period (of a relatively stationarity frequency structure). Findings also demonstrate a second non-stationarity between the NAO and European rainfall, producing considerable uncertainties in the detection of lags between multiannual NAO periodicities and water resource response. At present, there is limited atmospheric research to explain these modes of non-stationarity in the NAO and their influence on water resources, which poses a substantial challenge to the application of these multiannual periodicities in water resource forecasting systems. Future cross-discipline work between atmospheric and hydrological sciences may be needed to account for these non-stationaries, and to better understand how the relationship between multiannual NAO periodicities and water resource response may be used in the forecasting of water resource behaviours.
Keywords: Groundwater; streamflow; teleconnections; droughts; water resources; europe; United Kingdom; North Atlantic oscillation; wavelet transform